PENERAPAN E-GOVERNMENT DALAM PELAYANAN PUBLIK DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) KABUPATEN BATANG - Maulani, Wihda (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
E-Government is an information technology system used by the government to help improve public services. One of the district/city governments that implements E-Government is the Batang district government. The Investment and One-Stop Integrated Service Office (DPMPTSP) has an online licensing service, namely the SIPUAS licensing application (Business and Investment Licensing Service Information System). This article will discuss the implementation of E-government at the Batang Regency DPMPTSP through the SIPUAS application, which is an innovation in Electronic Government-based services with the aim of creating better service quality. The research method in this article uses a qualitative method using a literature study method. To see how the implementation of e-government in the SIPUAS application will use indicators (1) efficiency, (2) effectiveness, (3) transparency (Azkiya, 2018). The conclusion of the results of this study is that first, seen from the efficiency indicator of the use of the SIPUAS application, it can make it easier for the public because it can be accessed anywhere and can save costs and time. The menu on the SIPUAS application is also easy for the public to access. Second, seen from the effectiveness indicator of the implementation of the SIPUAS application by the Batang Regency DPMPTSP as explained above, this can make it easier for the public to apply for permits and avoid brokering. The results of the Public Satisfaction Survey on the services of the Batang Regency DPMPTSP in 2023 produced a Public Satisfaction Index (IKM) with a value of 90.93 (very good) (ptsp.batangkab.go.id, 2024). Third, seen from the transparency indicator. This SIPUAS application can be accessed openly and easily by the public. If you want to access this application, you can go directly to the website https://sipuas.batangkab.go.id/ or via the menu on the Batang Regency DPMPTSP website https://ptsp.batangkab.go.id/..